Prevalence and Distribution of African Swine Fever Virus in Swine Feed After Mixing and Feed Batch Sequencing - C. Grace Elijah; Jessie D. Trujillo; Cassandra K. Jones; Taeyong Kwon; Charles R. Stark; Konner R. Cool; Chad B. Paulk; Natasha N. Gaudreault; Jason C. Woodworth; Igor Morozov; Carmen Gallardo; Jordan T. Gebhardt; et al. (Kansas Agricultural Experiment Station Research Reports, 2021)
As the United States maintains trade with countries where African swine fever virus (ASFV) is endemic, it is critical to have methods that can detect and mitigate the risk of ASFV in potentially contaminated feed or ingredients. Therefore, the objectives of this study were to 1) evaluate feed batch sequencing as a mitigation technique for ASFV contamination in a feed mill, and 2) determine if a feed sampling method could identify ASFV following experimental inoculation. Batches of feed were manufactured in a BSL-3Ag room at Kansas State University’s Biosafety Research Institute in Manhattan, KS. First, the pilot feed manufacturing system mixed, conveyed, and discharged an ASFV-free diet. Next, a diet was manufactured using the same equipment, but contained feed inoculated with ASFV for a final concentration of 5.6 × 104TCID50/g. Then, four subsequent ASFV-free batches of feed were manufactured. After discharging each batch into a biohazard tote, 10 samples were collected in a double ‘X’ pattern. Samples were analyzed using a qPCR assay specific for the ASFV p72 gene to determine the cycle threshold (Ct) and log10genomic copy number (CN)/g of feed. Batch of feed affected the qPCR Ct values (P<0.0001) and the log10genomic CN/g (P<0.0001) content of feed. Feed samples obtained after manufacturing the ASFV-contaminated diet contained the greatest (P<0.05) amounts of ASFV p72 DNA across all criteria. Quantity of ASFV p72 DNA decreased sequentially as additional batches of initially ASFV-free feed were manufactured, but it was still detectable after batch sequence 4, suggesting cross contamination between batches. This subsampling method was able to identify ASFV genetic material in feed samples using the PCR assay specific for the ASFV p72 gene. In summary, sequencing batches of feed decreases concentration of ASFV contamination in feed, but does not eliminate it. Bulk ingredients or feed can be accurately evaluated for ASFV contamination by collecting 10 evenly distributed subsamples, representing 0.05% of the volume of the container, using the sampling method described herein.
Keywords: swine; African swine fever virus; feed safety